Contrasting confocal XRF with micro-SORS: a deep view within micrometric painted stratigraphy. Issue 31 (27th July 2018) - Conti, Claudia; Botteon, Alessandra; Colombo, Chiara; Realini, Marco; Matousek, Pavel; Vandenabeele, Peter; Laforce, Brecht; Vekemans, Bart; Vincze, Laszlo
Abstract : The study presents the application of combined micro-Spatially Offset Raman Spectroscopy (micro-SORS) and confocal X-ray fluorescence (confocal XRF) to the non-destructive investigation of micrometer scale stratified painted systems. Abstract : The study presents the application of combined micro-Spatially Offset Raman Spectroscopy (micro-SORS) and confocal X-ray fluorescence (confocal XRF) to the non-destructive investigation of micrometer scale stratified painted systems. Micro-SORS can be applied in situations where a high turbidity of layers prevents the acquisition of conventional Raman signals from depth and in the presence of Raman scattering compounds, facilitating highly chemically specific (molecular) characterization of the layers. In contrast, confocal XRF provides elemental information on a well-defined volume at a given depth. In this study, selected specimens have been analysed with both methods; molecular and elemental data have been compared and integrated for a comprehensive characterization of the stratigraphy. This dual approach represents a new analytical modality in the area of Cultural Heritage and is also beneficial in areas where non-destructive interrogation of thin layers and films is required.